Resilient Traditions, Modern Realities - Jamilah, Maryam; Ananda, Satria; Asrinaldi, Asrinaldi (Journal of Southeast Asian Human Rights, 2024)
This study explores the political economy of Minangkabau, a culturally rich and the world’s largest matrilineal community. The research focuses on understanding the power dynamics between men and women by conducting a gender analysis. The findings reveal that Minangkabau women hold a unique and privileged societal position. Traditionally, societal expectations allocate more roles and responsibilities to men, particularly in economic and political domains. Contemporarily, the special rights held by women have faded and been replaced by dominant male gender roles. Some gender roles have begun to disappear, such as the role of Bundo kanduang, mamak and tigo tungku sajarangan. In accessing economic resources, Minangkabau women experience challenges from men, private parties, and the government. These ignore the role of women as the legitimate owners of inherited property in Minangkabau land. Meanwhile, Minangkabau women have difficulty competing with men within systems that tend to be biased for political resources. In addition, Minangkabau women increasingly participate in productive work, demonstrating their ability to compete with men in the labor market. Despite these advancements, the study highlights a challenge for Minangkabau women. Keywords: Matrilineal, Gender, Political Economy, Gender Roles, Resources, Gender Division of Labor